Academic grit and subjective well-being in school: A study of students in a modern pesantren - Puspita Adhi Kusuma Wijayanti; Safarin Fitri Akmal (Jurnal Psikologi Terapan dan Pendidikan, 2026)
Twelfth-grade students in modern pesantren often face stricter regulations and higher academic demands than those in regular schools, as they are required to follow both national and religious curricula within a residential setting. These conditions may influence students’ subjective well-being in school. Previous research has suggested that academic grit is associated with students’ well-being, particularly in high-demand educational contexts. This study aimed to examine the relationship between academic grit and subjective well-being in school among students in a modern pesantren. A quantitative correlational design was employed, involving 97 twelfth-grade students. Academic grit was measured using the Academic Grit Scale, and subjective well-being in school was assessed using the Brief Adolescents’ Subjective Well-Being in School Scale. The results indicated a significant positive relationship between academic grit and subjective well-being in school. All dimensions of academic grit were significantly correlated with subjective well-being, with determination showing the strongest association. These findings highlight the role of academic grit as an important psychological resource in supporting students’ well-being in demanding educational environments. Additionally, supplementary findings revealed that peer relationships were the most influential factor contributing to students’ positive emotional experiences. These results underscore the importance of both individual and social factors in promoting well-being among students in pesantren settings.